2021
DOI: 10.3390/v13040668
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down and Bottom-Up Proteomics Methods to Study RNA Virus Biology

Abstract: RNA viruses cause a wide range of human diseases that are associated with high mortality and morbidity. In the past decades, the rise of genetic-based screening methods and high-throughput sequencing approaches allowed the uncovering of unique and elusive aspects of RNA virus replication and pathogenesis at an unprecedented scale. However, viruses often hijack critical host functions or trigger pathological dysfunctions, perturbing cellular proteostasis, macromolecular complex organization or stoichiometry, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 168 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…However, this approach typically requires some form of charge state stabilization or extremely high m/z resolution from the instrument ( 44 ). Often, top-down approaches are combined with tandem MS methods to distinguish between protein species and various modifications can be both located and identified ( 41 ).…”
Section: Modern Proteomics In the Microbiology Sequencing Eramentioning
confidence: 99%
See 2 more Smart Citations
“…However, this approach typically requires some form of charge state stabilization or extremely high m/z resolution from the instrument ( 44 ). Often, top-down approaches are combined with tandem MS methods to distinguish between protein species and various modifications can be both located and identified ( 41 ).…”
Section: Modern Proteomics In the Microbiology Sequencing Eramentioning
confidence: 99%
“…Regarding the topic of this review, in vivo XL-MS is a promising tool to discover virus–host associations and pathways ( 50 ), as well as potential interfaces for drug design or to derive a drug’s mode of action. With regards to drug discovery, nuclear magnetic resonance (NMR) and X-ray crystallography are still the structural methods of choice in a hit-to-lead or lead optimization strategy, however, native MS and hydrogen–deuterium exchange have been used as alternative methods and are regularly employed by biopharma companies ( 41 ).…”
Section: Modern Proteomics In the Microbiology Sequencing Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we aim to investigate the dynamics of in vitro processing of SARS-CoV-2 nsp7-11 with native mass spectrometry (MS). Native MS is a highly sensitive method allowing simultaneous monitoring of cleavage products making it very versatile to study dynamic and heterogenous processes 14 . Since in native MS, the natural folding and protein-protein interactions are preserved 15 , the protein complexes formed by the processing products can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…This group observed that the BRD4 inhibitors disrupted binding to acetylated transcriptional regulators. This study is complemented by a review by Simanjuntak et al [ 7 ] that describes novel MS tools to study the structure and composition of protein complexes, providing critical mechanistic insights into their functions. New approaches in top-down and bottom-up mass spectrometry-based are presented to identify novel- and tractable antiviral targets.…”
mentioning
confidence: 99%